Penerapan Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V - Suhaini, Siti Herli; Mustika, Dea (Jayapangus Press, 2025)
Science education in elementary school is crucial for fostering students' scientific understanding and critical thinking skills. However, the low learning outcomes in science among fifth-grade students at SDN 001 Lubuk Terap, evidenced by scores below the Minimum Completeness Criteria (KKM) and less varied teaching methods, poses a significant problem. This study aimed to investigate the effectiveness of the Student Teams Achievement Divisions (STAD) cooperative learning model in improving students' science learning outcomes. Employing a Classroom Action Research (CAR) approach with two cycles at SDN 001 Lubuk Terap, this study involved 24 fifth-grade students. Data were collected through observation, tests, and documentation, then analyzed qualitatively and quantitatively. The results indicated a significant improvement in both teacher and student activities, as well as overall student learning outcomes. This was reflected by teacher and student activity percentages exceeding 90% in the